PERLINDUNGAN HUKUM TERHADAP HASIL PRODUKSI USAHA MIKRO KECIL DAN MENENGAH MELALUI PENDAFTARAN HAK MEREK DI KABUPATEN GIANYAR - Anggreni, Ni Made Manik; Citra, Made Emy Andayani (Jurnal Hukum Mahasiswa, 2024)
The purpose of this research is to find out, understand how legal protection is for MSME products in Gianyar Regency and to find out what influences business actors not to register their trademarks. The research used in this research is a type of empirical legal research. The problem approach used by the author in writing this legal research is using the fact approach (The Fact Approach) and the Statute Approach. The fact approach is an approach whose implementation uses data collection techniques based on facts regarding real conditions or actual conditions that occur. in the field. Brand protection is provided when there is a brand violation committed by a party who does not have the rights to a brand. The factors that influence business actors not to register their trademarks are external and internal factors.